PECIPTA 2015 - USM WINS EIGHT GOLD MEDALS AND A SPECIAL AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUALA LUMPUR, 6 December 2015 Universiti Sains Malaysia (USM) excelled at the 14th International Higher Education Institutions Research and Invention Expo (PECIPTA 2015) by winning eight gold medals and one special award, in addition to seven silver and seven bronze medals.